2019
DOI: 10.3389/fneur.2018.01199
|View full text |Cite
|
Sign up to set email alerts
|

ZEB1 Is a Transcription Factor That Is Prognostic and Predictive in Diffuse Gliomas

Abstract: Objective: To address the unmet medical need to better prognosticate patients with diffuse gliomas and to predict responses to chemotherapy regimens.Methods: ZEB1 alterations were retrospectively identified from a cohort of 1,160 diffuse glioma patients. Epigenome-wide association scans (EWAS) were performed on available data. We determined the utility of ZEB1 as a prognostic indicator of patient survival in diffuse gliomas and assessed the value of ZEB1 to predict the efficacy of treating diffuse glioma patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…In hepatocarcinoma cells, ZEB1 regulated the resistance of Dox and mediated the mesenchymal characteristics 31. In glioma, ZEB1 acted as a transcription factor of Prognosis and Predict 32. Consistent with all the findings, ZEB1 was overexpressed in OC tissues and cell lines, and upregulation of ZEB1 predicted poor prognosis.…”
Section: Discussionsupporting
confidence: 74%
“…In hepatocarcinoma cells, ZEB1 regulated the resistance of Dox and mediated the mesenchymal characteristics 31. In glioma, ZEB1 acted as a transcription factor of Prognosis and Predict 32. Consistent with all the findings, ZEB1 was overexpressed in OC tissues and cell lines, and upregulation of ZEB1 predicted poor prognosis.…”
Section: Discussionsupporting
confidence: 74%
“…CHAC1 functioned in the temozolomide response [ 34 ]. Notably, ZEB1 was widely recognized as an accelerating factor for the genesis and invasion of GBM and was inversely correlated with survival [ 35 , 36 ]. In comparison, we found that ZEB1 expression was protective in the risk score.…”
Section: Discussionmentioning
confidence: 99%
“…Five-week-old male BALB/c nude mice (Beijing Vital River Laboratory Animal Technology Co., Ltd.) were randomized into two groups (n=5 per group, total=10). Tumor cells (5×10 6 ) were injected into right dorsal flanks of blindly randomized nude mice (n=5, 1×10 6 per mice), respectively. Every 5 days, we measured the tumor's longitudinal diameter and latitudinal diameter using a caliper.…”
Section: Animal Studymentioning
confidence: 99%
“…Transcription factors (TFs) are major contributors to cancer progression and prognosis [4,5]. For instance, Edwards et al revealed that ZEB1 serves as a TF that is prognostic and predictive in diffuse gliomas [6]. Oktay et al indicated that thyroid TF-1 plays a key role in lung adenocarcinoma prognosis [7].…”
Section: Introductionmentioning
confidence: 99%